The imperial game : cricket, culture and society - Stoddart, Brian; Sandiford, Keith A. P., 1936- (Manchester University Press, 2017)
This anthology examines the fortunes of cricket in various colonies as the sport spread across the British Empire. It helps to explain why cricket was so successful, even in places like India, Pakistan and the West Indies where the Anglo-Saxon element remained in a small minority. It demonstrates, perhaps better than any other single work, how awesome was the power of cultural imperialism. Even when former subjects threw off the political yoke of the Europeans, they still adhered tenaciously to the sporting and recreational models that the imperialists had introduced. 'The Imperial Game' provides an invaluable insight into how cricket developed powerful social, cultural and even political connotations in a colonial environment. This is a fascinating study of cricket as a cultural phenomenon, and traces its changing meaning in all the continents in which Britain once exercised power. The book is a collection of essays by six of the world's leading scholars in the field of sports history, and will be of value not onle to students examining the historical sociology of sport, but also to those with a general interest in social history. This study will also appeal to cricket enthusiasts the world over.
Includes index.
Keywords: Cricket -- Colonies -- Great Britain -- Social aspects.; Cricket -- Great Britain -- Colonies -- History -- 19th century.; Cricket -- Great Britain -- Colonies -- History -- 20th century.; Cricket -- Colonies -- Aspect social -- Grande-Bretagne.; Cricket -- Grande-Bretagne -- Colonies -- Histoire -- 19e siècle.; Cricket -- Grande-Bretagne -- Colonies -- Histoire -- 20e siècle.; History /Colonialism & Imperialism.; HISTORY -- Europe -- Great Britain.; HISTORY / Europe / Great Britain / General; Cricket -- British colonies; Great Britain; History.; 1800-1999; Electronic books; History